Pengembangan Model Pembelajaran Diskusi dan Personal Investigation Berbasis E-Learning terhadap Domain Psikomotorik Siswa di SMK Negeri 1 Kota Jambi - Redi Indra Yudha; Ulul Azmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The learning model itself has many types, designs and forms that can be selected according to the situation, conditions, time and place of implementation of the implementation of the learning model. In fact, the use of the learning model itself tends to be an option for a teacher when teaching and learning activities take place so that the delivery of material can be more optimal, moreover the learning is held in a class that is large enough and requires facilities so that the delivery of material can be carried out properly. The psychomotor domain of most of the students in both the control and experimental classes was the same. That is, the ability to apply the message from the material presented will not necessarily succeed if it only relies on intelligence alone if it is not accompanied by better direction, apart from the intervention of the teacher in the field of study concerned so that students are better at working on practical questions better. Thus, the ability of students is not only measured by the extent to which they are able to know, understand, and absorb new sources of information from messages conveyed on the subject matter given alone. However, the benchmark of how and to what extent students will be able to apply to a problem at hand must certainly be considered again, especially in teaching and learning activities through e-learning.